Correction: One-pot construction of functionalized aziridines and maleimides via a novel pseudo-Knoevenagel cascade reaction. Issue 14 (7th February 2020) - Lei, Jie; Song, Gui-Ting; He, Liu-Jun; Luo, Ya-Fei; Tang, Dian-Yong; Lin, Hui-Kuan; Frett, Brendan; Li, Hong-yu; Chen, Zhong-Zhu; Xu, Zhi-Gang
Abstract : Correction for 'One-pot construction of functionalized aziridines and maleimides via a novel pseudo-Knoevenagel cascade reaction' by Jie Lei et al., Chem. Commun., 2020, DOI: ; 10.1039/c9cc08220d .